2019
DOI: 10.1177/2050312119874995
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing physical activity in patients with early rheumatoid arthritis: A mixed-methods study

Abstract: Objective: The goal of this study was to provide a greater understanding of physical activity in patients with early rheumatoid arthritis. The aim was twofold: first to explore if physical activity was associated with factors in the clinical picture of rheumatoid arthritis in this patient group, and second, to explore factors influencing physical activity in patients with early rheumatoid arthritis. Methods: A total of 66 patients with early rheumatoid arthritis were included in the study. A sequential explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
1
6
1
1
Order By: Relevance
“…This might be due to the fact that retired people are older and have a higher disease activity, as shown by our data. However, the finding contradicts the study of Qvarfordt et al [58], who reported that RA patients who were working and those on sick leave failed to fulfill the recommendations, whereas retired patients were more likely to meet the recommendations. The authors hypothesized that retired RA patients had more free time for physical activity than those who were working.…”
Section: Discussioncontrasting
confidence: 86%
“…This might be due to the fact that retired people are older and have a higher disease activity, as shown by our data. However, the finding contradicts the study of Qvarfordt et al [58], who reported that RA patients who were working and those on sick leave failed to fulfill the recommendations, whereas retired patients were more likely to meet the recommendations. The authors hypothesized that retired RA patients had more free time for physical activity than those who were working.…”
Section: Discussioncontrasting
confidence: 86%
“…In another study of 573 individuals with RA, 94% of the participants were Caucasian [ 50 ].Of the physical variables, functional disability was the most consistent and negative correlate of PA parameters (60%, n = 18/30). Although the findings were more inconsistent when considering the most adjusted or final model statistics, this finding corroborates recent reports linking worse physical functioning to lower levels of PA in those with early RA [ 88 ] and PA maintenance over a 7-year period [ 89 ]. Further, fatigue was negatively related to PA (61%, n = 11/18), yet the results may be distorted due to one study [ 55 ] utilizing the five separate domains of the MFI-20.…”
Section: Discussionsupporting
confidence: 85%
“…Even though smoking is considered one of the main environmental risk factors of RA, vitamin D is also a potential factor [9]. On the other hand, since RA restricts mobility, affected patients restrict their outdoor activities [14]. This, in turn, limits their sun exposure, which is the main source of vitamin D. Further deficiency of this vitamin could also exacerbate the disease.…”
Section: Discussionmentioning
confidence: 99%